Three philosophies of life : Ecclesiastes--life as vanity, Job--life as suffering, Song of Songs--life as love - Kreeft, Peter (San Francisco, Ignatius Press, 1989)
"I've been a philosopher for all my adult life and the three most profound books of philosophy that I have ever read are Ecclesiastes, Job, and Song of Songs." These are the opening lines of Kreeft's Three Philosophies of Life. He reflects that there are ultimately only three philosophies of life and each one is represented by one of these books of the Bible-life is vanity; life is suffering; life is love. In these three books Kreeft shows how we have Dante's great epic The Divine Comedy played out, from Hell to Purgatory to Heaven. But it is an epic played out in our hearts and lives, here and now. Just as there is movement in Dante's epic, so there is movement in these books, from Ecclesiates to Job, from Job to Song of Songs. Love is the final answer to Ecclesiastes' quest, the alternative to vanity, and the true meaning of life. Finally, Kreeft sees in these books the epitome of theological virtues of faith, hope and love and "an essential summary of the spiritual history of the world."
Ecclesiastes : life as vanity -- Job : life as suffering -- Song of songs : life as love
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Criticism, interpretation, etc